2010
DOI: 10.1186/1479-5876-8-48
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-206 in the skeletal muscle from myotonic dystrophy type 1 patients

Abstract: BackgroundMicroRNAs are highly conserved, noncoding RNAs involved in post-transcriptional gene silencing. They have been shown to participate in a wide range of biological processes, including myogenesis and muscle regeneration. The goal of this study is to test the hypothesis that myo-miRs (myo = muscle + miR = miRNA) expression is altered in muscle from patients affected by myotonic dystrophy type 1 (DM1), the most frequently inherited neuromuscular disease in adults. In order to gain better insights about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 48 publications
3
67
0
1
Order By: Relevance
“…Gambardella et al [74] detected overexpression of miR-206 in the skeletal muscle from myotonic dystrophy type 1 (Dm1) patients. ISH localized miR-206 to the nucleus in both normal and Dm1 tissues.…”
Section: Mirna Ish Application In Human Diseasesmentioning
confidence: 99%
“…Gambardella et al [74] detected overexpression of miR-206 in the skeletal muscle from myotonic dystrophy type 1 (Dm1) patients. ISH localized miR-206 to the nucleus in both normal and Dm1 tissues.…”
Section: Mirna Ish Application In Human Diseasesmentioning
confidence: 99%
“…In DM1 skeletal muscle biopsies, microRNA (miR) expression patterns are variable between studies with miR-206 overexpression compared to controls (Gambardella et al, 2010) while another study found that miR-1 and miR-335 were upregulated, miRs 29b,c and miR-33 were downregulated, and miR-1, miR133b and miR-206 were mislocalized (Perbellini et al, 2011). Mis-processing of miR-1 occurs in the DM1 heart and this has been linked to MBNL loss-of-function.…”
Section: 2 Rna Toxicity and Protein Sequestration In Myotonic Dystrmentioning
confidence: 99%
“…They proposed that MBNL1 sequestration in DM1 allowed LIN28 to bind and repress synthesis of miR-1 in DM1 cardiac tissues and increased expression of miR-1 targets such as connexin 43 resulting in cardiac pathology. As yet, there is no consensus with regard to miRNA levels in DM1 skeletal muscles [38 ▪ ,39 ▪ ]. Nevertheless, these studies highlight the potential role of miRNAs in DM1.…”
Section: Things Are Never As Easy As They Seemmentioning
confidence: 99%